Pelanggaran Hak Asasi Manusia oleh Milisi dalam Perang Saudara di Nigeria - Marten Karelauw; Arman Anwar; Veriena Josepha Batseba Rehatta (Faculty of Law, Universitas Pattimura, 2022)
Introduction: Militia can serve as a supplement to the regular military, or they can oppose it, for example against military coups.Purposes of the Research: This writing aims to analyze and examine how the international legal arrangements regarding militias in a country. Methods of the Research: The research method in this paper uses a prescriptive analytical research type. The research approach used is a statutory approach, a conceptual approach and a case approach. The procedure for collecting legal materials uses primary legal materials and secondary legal materials through books, articles, journals and the writings of legal experts, as well as legal materials analysis techniques in this study using qualitative analysis techniques.Results of the Research: The result obtained is the regulation of human rights violations by militias in the civil war in Nigeria, specifically regulated in Article 3 of the 1949 Geneva Conventions concerning the obligations of parties to non-international armed conflicts that take place in the territory of one of the High Contracting Parties. And Additional Protocol II of 1977 as a complement to the 1949 Geneva Conventions which regulates armed conflicts that are not international in nature. Based on the provisions of the convention and the Additional Protocol, in its implementation in armed conflict by militias in Nigeria, various human rights violations by militias were found. So it is necessary to have an active role from international organizations in enforcement and protection efforts, as a form of role in creating peace for the parties.